2016
DOI: 10.1107/s2059798316016715
|View full text |Cite
|
Sign up to set email alerts
|

Quadruple space-group ambiguity owing to rotational and translational noncrystallographic symmetry in human liver fructose-1,6-bisphosphatase

Abstract: Fructose-1,6-bisphosphatase (FBPase) is a key regulator of gluconeogenesis and a potential drug target for type 2 diabetes. FBPase is a homotetramer of 222 symmetry with a major and a minor dimer interface. The dimers connected via the minor interface can rotate with respect to each other, leading to the inactive T-state and active R-state conformations of FBPase. Here, the first crystal structure of human liver FBPase in the R-state conformation is presented, determined at a resolution of 2.2 Å in a tetragona… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
5
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 58 publications
1
5
0
Order By: Relevance
“…The profile of the deconvoluted spectra fitted the observed peaks very closely, as shown in Figure S3. The analysis indicated that a fraction of the complex is associated with magnesium ions, in accordance with the tendency of this complex to bind three divalent metal ions per subunit. , The stoichiometry of the FBP1 complex remained stable despite the exposure of yeast cells to heat shock or to the glucose-containing medium, suggesting that stoichiometry is not used to regulate the complex. However, a distinct pattern of modifications could be identified under each growth condition.…”
Section: Resultssupporting
confidence: 76%
See 1 more Smart Citation
“…The profile of the deconvoluted spectra fitted the observed peaks very closely, as shown in Figure S3. The analysis indicated that a fraction of the complex is associated with magnesium ions, in accordance with the tendency of this complex to bind three divalent metal ions per subunit. , The stoichiometry of the FBP1 complex remained stable despite the exposure of yeast cells to heat shock or to the glucose-containing medium, suggesting that stoichiometry is not used to regulate the complex. However, a distinct pattern of modifications could be identified under each growth condition.…”
Section: Resultssupporting
confidence: 76%
“…S3. The analysis indicated that a fraction of the complex is associated with magnesium ions, in accordance with the tendency of this complex to bind three divalent metal ions per subunit3031. The stoichiometry of the FBP1 complex remained stable despite the exposure of yeast cells to heat shock or to the glucose-containing medium, suggesting that stoichiometry is not used to regulate the complex.…”
Section: Resultsmentioning
confidence: 75%
“…The catalytically inactive FBP1 E98A variant binds ALDOB and PP2A-C and inhibits AKT activation as effectively as the native protein, but human FBP1 missense mutants that are not severely destabilized, L329P, R158W, G164S and N213K, are devoid of AKT inhibitory activity. One of the residues affected by these mutations, L329, is not a part of the catalytic pocket (Huang et al, 2020; Ruf et al, 2016) and is associated with only a modest decrease in FBPase activity, underscoring the disconnect between loss of GNG and insulin hyperresponsiveness. Mass spectrometry, IP, gel filtration and PLA demonstrated that FBP1 is the lynchpin responsible for formation of the FBP1:AKT:PP2A-C:ALDOB regulatory complex that is destabilized by insulin to facilitate AKT activation.…”
Section: Discussionmentioning
confidence: 99%
“…Fructose-1,6-bisphosphatase (FBPase) with bound adenosine monophosphate (AMP) in the T (inactive) state resulted in a crystal with four possible space groups P4 1 22, P4 3 22, P4 1 2 1 2 and P4 3 2 1 2 [89]. For this crystal, tNCS related elements resulted in a unit cell that was 3x longer in the c dimension than what may have been initially estimated.…”
Section: Fbpase-mentioning
confidence: 99%